Service Learning Educational Community School of Occupational Therapy, Andrés Bello University, Viña del Mar campus. - Puntareli Vicencio, Bianca; Santander Catrín, Carolina; Schiller Oyarzún, Cynthia (Relatos Journal, 2024)
Within the framework of an educational innovation project at the Andrés Bello University (UNAB), the development of a didactic experience was promoted in the subject of Procesos de Terapia Ocupacional II (taken in the sixth semester) of the Occupational Therapy (OT) degree at the Viña del Mar campus, so that the students could implement, through the support of a teaching guide, the Service-Learning (SL) Methodology, with a group of first-year students, who voluntarily agreed to be part of the initiative.The innovation was located, not only in the implementation of the SL Methodology, but also in including the student community itself (first year) as a recipient agent of the intervention, which relieves the responsibility and social commitment of this innovation, consistent with the graduation profile of the degree.The beginning of the experience contemplated support from the teachers, however, as the experience progressed, the autonomy and leadership of the educational community was progressively enhanced, making them responsible for the process so that they are able to address problems or needs in the community, while acquiring knowledge and skills related to their academic curriculum.
Keywords: Service Learning; Student Community; Higher Education